Finding the Right Balance: A Social Norms Intervention to Reduce Heavy Drinking in University Students - Wolter, Christine; Lesener, Tino; Thomas, Tobias Alexander; Hentschel, Alicia-Carolin; Gusy, Burkhard (Frontiers in Public Health, 2021)
Introduction: Heavy alcohol consumption constitutes a major health risk among University students. Social relationships with peers strongly affect University students' perception of the drinking behavior of others, which in turn plays a crucial role in determining their own alcohol intake. University students tend to overestimate their peers' alcohol consumption – a belief that is associated with an increase in an individual's own consumption. Therefore, we implemented a social norms intervention with personalized normative feedback at a major University in Germany to reduce and prevent excessive drinking among University students. Methods: Our intervention was part of a regular health monitoring survey. We invited all enrolled University students to take part in this survey on two occasions. A total of 862 University students completed the questionnaire, 563 (65.3%) of which received e-mail-based feedback upon request concerning their peers' and their own alcohol consumption. For the intervention group (n = 190) as well as the control group (no feedback requested; n = 101), we included only University students in the evaluation who overestimated their peers' alcohol use and indicated above average consumption of the peers. We applied analyses of variance to assess intervention effects with regard to the correction of overestimated group norms as well as University students' drinking behavior. Results: Within the intervention group, we observed a significantly larger reduction of the previously overestimated behavioral norms compared to the control group (p < 0.001; ηp2 = 0.06). With regard to behavioral outcomes the intervention group showed a significantly larger reduction in the AUDIT-C score (p = 0.020; ηp2 = 0.03). Discussion: Our study confirms previous research whereupon personalized, gender-specific and selective normative feedback is effective for alcohol prevention among University students. However, University students still overestimated their peers' alcohol intake after the intervention. Furthermore, we did not reach high-risk groups (University students with the highest alcohol intake) since no feedback was requested. Future studies should address factors influencing the impact of the intervention and reachability of selective groups.